Globally exponential synchronization criterion of chaot-ic oscillators using active control - Ahmad, Israr; Al Mahrouqi, Sharifa; Shahzad, Mohammad (International Journal of Advanced Mathematical Sciences, 2017)
This research paper focuses the globally exponential synchronization between two identical and two nonidentical chaotic oscillators. With the help of Lyapunov direct method and using the active control technique, suitable algebraic conditions are obtained analytically that establish the globally exponential synchronization. The proposed globally exponential synchronization criterion is more general and much less conservative than the previously published works. A comparison, based upon the synchronization speed, cost and quality have been performed with our study of the previously published results. The effect of unknown external disturbances has also been discussed. Numerical simulation results are presented to illustrate the performance and efficiency of this study.